2020
DOI: 10.3390/en14010080
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Nanofluids on Droplet/Spray Cooling of a Heated Surface: A Critical Review

Abstract: Cooling by impinging droplets has been the subject of several studies for decades and still is, and, in the last few years, the potential heat transfer enhancement obtained thanks to nanofluids’ use has received increased interest. Indeed, the use of high thermal conductivity fluids, such as nanofluids’, is considered today as a possible way to strongly enhance this heat transfer process. This enhancement is related to several physical mechanisms. It is linked to the nanofluids’ rheology, their degree of stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 184 publications
0
23
0
Order By: Relevance
“…Droplet splashing and manipulation onto surfaces is a key phenomenon for applications such as microfluidic systems, microreactors and electronic refrigerators [141,142]. Tailoring the chemistry and topography can lead to the design of non-wetting surfaces with substantially diminished contact when exposed to liquids performing as, for example, excellent lubricants [143].…”
Section: Slippery Surfacesmentioning
confidence: 99%
“…Droplet splashing and manipulation onto surfaces is a key phenomenon for applications such as microfluidic systems, microreactors and electronic refrigerators [141,142]. Tailoring the chemistry and topography can lead to the design of non-wetting surfaces with substantially diminished contact when exposed to liquids performing as, for example, excellent lubricants [143].…”
Section: Slippery Surfacesmentioning
confidence: 99%
“…Nonetheless, most of the droplets still adhered to the heated surface, thereby increasing the wetted area for cooling purposes. Aksoy et al 18 conducted a review of the published literature on nanofluid spray cooling, and concluded that nanofluids have a high potential for improving the heat transfer performance of spray cooling systems. However, they argued that further experimental research is required to determine the performance and operational limits of such fluids when cooling via droplet impact.…”
Section: Introductionmentioning
confidence: 99%
“…Droplet impact onto solid surfaces is a very popular research field thanks to an extensive variety of applications with the examples including surface coating, 1 forensic science, 2 inkjet printing, 3,4 and spray cooling. [5][6][7][8] In particular, the maximum spreading ratio β max , i.e., the ratio of the maximum spreading diameter D m to the initial droplet diameter D 0 , determines the performance of these processes. 9 As the fluid and surface properties govern droplet spreading, the following non-dimensional numbers must be considered for its modeling:…”
Section: Introductionmentioning
confidence: 99%